H=3c+2b/4 if that is correctly what you said
Start by moving everything that is not b to the other side
H-3c= 2b/4
Then multiply by 4 on both sides to get ride of fraction on left
4(H-3c)=2b
Then divide by 2 to get b
(4(H-3c))/2=b
You can then simplify the fractions
2(H-3c)=b >>> 2H-6c=b
If your equation was this
H=(3c+2b)/4
You multiply 4 on both sides
4H=3c+2b
You then push evey thing thats not b to the left
4H-3c=2b
Then divide by two to get answer
(4H-3c)/2=b
2006-12-17 11:10:35
·
answer #1
·
answered by TheThing 2
·
0⤊
0⤋
Let me give you the steps so that you do not have to question anymore.
Given:
H = (3c + 2b) / 4
(1) Multiply both sides of the equation by 4
4H = 3c +2b (Note: at the right side of the equation 4/4 = 1)
(2) Subtract 3c from both sides of the equation (Simply transpose 3c to the left and change the sign)
4H - 3c = 3c -3c +2b
4H - 3c = 0 + 2b
(3) Flip Flop the equation
0 + 2b = 4H - 3c
2b = 4H - 3c
(4) Divide both sides of the equation by 2
2b / 2 = (4H - 3c) / 2
(5) Simplify
b = (4H - 3c) / 2 (Note: at the left side of the equation, 2/2 = 1)
Moral:
Transform any fractional equation to linear equation by either multiplying or dividing the constant or expression by itself to reduce to 1.
2006-12-17 19:24:18
·
answer #2
·
answered by ATIJRTX 4
·
0⤊
0⤋
So, you have
H=3c+2b over 4
4H=3c+2b Multiply both sides by 4 to get rid of denominator
4H-3c=2b Subtract 3c
2H-3over2c=b or 2H-(3/2c)=b
2006-12-17 19:06:55
·
answer #3
·
answered by CC 2
·
0⤊
1⤋
You need to isolate the expression with b.
So the first thing is multiply by 4.
4H = 3c + 2b.
Now subtract 3c.
4H - 3c = 2b.
Finally, divide by 2.
(4H - 3c) / 2 = b
Hope that helps!
2006-12-17 19:05:26
·
answer #4
·
answered by teekshi33 4
·
1⤊
1⤋
if the question you are asking is H=(3c+2b)/4, then the answer is b=(4H-3c)/2.
2006-12-17 19:05:46
·
answer #5
·
answered by nateincincy 1
·
1⤊
1⤋
H = (3c + 2b)/4
4H = 3c + 2b
4H - 3c = 2b
(4H - 3c)/2 = b
2006-12-17 19:04:27
·
answer #6
·
answered by Tom :: Athier than Thou 6
·
0⤊
1⤋
got this
4h = 3c + 2b
4h - 3c = 2b
b = (4h - 3c) / 2
2006-12-17 19:03:57
·
answer #7
·
answered by Jake L 3
·
0⤊
1⤋
isn't there a second equation? or 3rd?
3 unknowns requires 3 equations
2006-12-17 19:10:02
·
answer #8
·
answered by Ted Jordan 5
·
0⤊
0⤋
first what is the value of c and b
2006-12-17 19:04:40
·
answer #9
·
answered by Arvind 2
·
0⤊
1⤋